Effects of low-dose irradiation on human osteoblasts and periodontal ligament cells - Jarinya Pathomburi (2020)
© 2019 Elsevier Ltd Objective: To investigate the effects of dental x-ray on proliferation and mineralization in human primary osteoblasts as well as on proliferation and apoptotic potential in human periodontal ligament (PDL) cells. Design: Primary osteoblasts and PDL cells were irradiated with various doses of periapical radiography by repeated exposures and further incubated for 1, 3 or 7 days. Cell proliferation was assayed by BrdU incorporation. The effect of dental x-ray on mineralization in osteoblasts either before or after x-ray exposures was determined by Alizarin red staining. Both mRNA and protein expressions of BCL-2, an anti-apoptotic gene, and BAX, a pro-apoptotic gene, in PDL cells were analyzed by RT-qPCR and immunoblotting analysis, respectively. Results: Neither the proliferative nor the mineralization ability of irradiated osteoblasts was different from that of non-irradiated osteoblasts at any doses or time points. By contrast, there was a significant decrease in the proliferation of PDL cells on day 3 after repeated exposures to dental x-ray for 20 times (P < 0.05), whereas the ratio of BCL-2 to BAX mRNA and protein expressions in these irradiated PDL cells was significantly increased (P < 0.05). Conclusions: Upon multiple exposures to dental x-ray used in intraoral radiography up to 20 times, there is no effect on the proliferation or the mineralization of osteoblasts, whereas the proliferative and apoptotic potentials of PDL cells are transiently decreased.